2007
DOI: 10.1016/j.neuroimage.2007.05.013
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput morphologic phenotyping of the mouse brain with magnetic resonance histology

Abstract: The Mouse Bioinformatics Research Network (MBIRN) has been established to integrate imaging studies of the mouse brain ranging from three-dimensional (3D) studies of the whole brain to focused regions at a sub-cellular scale. Magnetic resonance (MR) histology provides the entry point for many morphologic comparisons of the whole brain. We describe a standardized protocol that allows acquisition of 3D MR histology (43-micron resolution) images of the fixed, stained mouse brain with acquisition times < 30 minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 23 publications
0
132
0
Order By: Relevance
“…Imaging in the mouse requires significant hardware and sequence upgrades compared with standard human clinical scanners. However, despite the technical hurdles involved in mouse imaging, several mouse imaging centers have had success in imaging mouse brains with high neuroanatomical resolution [108][109][110][111][112][113], including ours at the Mouse Imaging Centre at the Hospital for Sick Children in Toronto [93,94,114].…”
Section: Discoveries Of Neuroanatomical Abnormalities In Mouse Modelsmentioning
confidence: 99%
“…Imaging in the mouse requires significant hardware and sequence upgrades compared with standard human clinical scanners. However, despite the technical hurdles involved in mouse imaging, several mouse imaging centers have had success in imaging mouse brains with high neuroanatomical resolution [108][109][110][111][112][113], including ours at the Mouse Imaging Centre at the Hospital for Sick Children in Toronto [93,94,114].…”
Section: Discoveries Of Neuroanatomical Abnormalities In Mouse Modelsmentioning
confidence: 99%
“…Finally, data were organized into a consistent file architecture and archived in NIfTI format (http:// nifti.nimh.nih.gov) in an on-site Oracle database. 34 …”
Section: Dti Processingmentioning
confidence: 99%
“…Most very high resolution rodent studies Benveniste et al, 2000;Johnson et al, 2007) have been performed on ex-vivo samples, allowing for long acquisition times without physiological noise or motion. Some of the advantages of imaging ex-vivo were demonstrated in a recent study (Jack et al, 2004(Jack et al, , 2005, where in Alzheimer mouse models amyloid plaques were identified using spin echo MRI.…”
Section: Introductionmentioning
confidence: 99%